A new species and a new record of Begonia (sect. Platycentrum, Begoniaceae) from northeastern India - Krishna, Nikhil; Pradeep, Ayilliath Kuttiyeri; Amrutha, Athalappil; Jayakrishnan, Thachat (Phytotaxa, 2021)
A new species of Begonia, Begonia murlenensis (sect. Platycentrum) is described and illustrated from northeastern India. The new species is compared with B. manhaoensis. Diagnostic characters are provided along with a distribution map and notes on its habitat and phenology. Begonia zhongyangiana as a new record in India is also presented here along with a distribution map.